Improving the processing of competition results using publicly available digital tools - Abrashina I.V.; Abrashin D.G. (Theory and Practice of Physical Culture, 2025)
Objective of the study is aimed at creating, arguing and implementing a digital model for calculating and analyzing the results of sports events, providing for the transformation of primary indicators into a point system using Microsoft Excel tools. Methods and structure of the study. The research and creation of the product was carried out on the basis of the Faculty of Physical Culture of the Leningrad State University named after A.S. Pushkin. The following criteria were defined in the terms of reference for this program: the ability to simultaneously register the results of competitions in nine disciplines; automatic conversion of recorded totals from time and numerical indicators into a point system with subsequent calculation of the arithmetic mean and rounding to an integer; consideration of gender and age of competitors in calculations; preventing accidental changes to the source data of the "standards" section when working with the program; providing the user with only basic information about the participants and the actual results of the competition as available functions. Results and conclusions. The presented competition data processing methodology, implemented in Microsoft Excel, provides recording of results in various formats, taking into account the gender and age categories of participants. It automatically converts time and numerical indicators into a point system, calculates the average value, rounding it to an integer. The product is designed with protection against unauthorized editing of primary data and adapts to various sports disciplines due to the easily changeable parameters on the "Standards" sheet. The practical value of this development was confirmed during the entrance exams in the subject "Physical Culture" at the LSU named after A.S. Pushkin in the period from 2021 to 2024, where the results were recorded in nine different sports exercises.